Meanings of death for adults with cancer assisted in an oncological hospital in Brazil. - Sartor, Silvia Francine (2021)
Objective: To know the meaning of death for hospitalized cancer adults. Method: This is a qualitative, descriptive study carried out with 27 patients at an Oncology Hospital in Brazil. The data were collected from December 2019 to March 2020 using two instruments: the sociodemographic and clinical profile of the participant, and a script for semi-structured interviews. Creswell’s content analysis method was used after classifying the data using the Iramuteq software. Results: Six classes emerged and were grouped by similar content, which made up four categories: death as a change of life and passage, death is better than suffering, the expectation of divine intervention, and death denied and distanced. Conclusion: The meaning of death moves from a passing process and a change in life to the origin of fear and insecurity. Patients have in God the support to face their illnesses and the worsening of the disease. In the hospital routine, death brings them closer to their existential experience.